The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1097/01.mlg.0000175679.68452.75
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal Cerebrospinal Fluid Leaks: Management of 97 Patients Over 10 Years

Abstract: In conclusion, our endoscopic repair rate for sinonasal CSF leaks are good and compare well with the standards in the literature. Raised ICP is the most common reason for recurrent CSF leak after repair. Patients with a spontaneous CSF leak and evidence of raised ICP had a 46% failure rate. When consenting such patients for surgery, they must be informed of the lower success rate and that they may need additional procedures, including shunting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
140
0
16

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(163 citation statements)
references
References 13 publications
(30 reference statements)
7
140
0
16
Order By: Relevance
“…Endoscopic repair of CSF leaks has a high rate of success and is currently the mainstay of repair of CSF leaks. [11][12][13][14] Our series demonstrated that MPR images from 0.625-and 1.25-mm collimated sections accurately characterized the size of skull base defects in 15 (75%) of 20 patients. Of our 19 patients, 10 had MPR images based on 0.625-mm axial datasets.…”
Section: Discussionmentioning
confidence: 64%
“…Endoscopic repair of CSF leaks has a high rate of success and is currently the mainstay of repair of CSF leaks. [11][12][13][14] Our series demonstrated that MPR images from 0.625-and 1.25-mm collimated sections accurately characterized the size of skull base defects in 15 (75%) of 20 patients. Of our 19 patients, 10 had MPR images based on 0.625-mm axial datasets.…”
Section: Discussionmentioning
confidence: 64%
“…4,8,12,16 This sequence of events results in effusions in the middle ear and mastoid air cells that can manifest as CSF fistulas, through a disrupted tympanic membrane or via the eustachian tube. [1][2][3]5,11,12,15 Given that intracranial hypertension has been implicated as a significant factor in temporal encephalocele formation, 7,[10][11][12]15 we hoped to clarify this correlation by reviewing a series of tegmen defects repaired surgically and the associated ICP measurements in these patients. Additionally, we aimed to determine the rate of and indications for VP shunt placement.…”
Section: Neurosurg Focus 32 (6):e6 2012mentioning
confidence: 99%
“…With a combined mastoid/middle fossa approach, we were able to achieve a high success rate (96%) of CSF fistula closure, comparable to rates in previously published reports. 2,5,8,13,14 Our surgical technique involves a robust dural closure following extradural dissection and encephalocele reduction/resection. We use a multilayer closure for direct repair of the dural and cranial base defects.…”
Section: Patient Outcomesmentioning
confidence: 99%
“…No está claro el uso de antimicrobianos sistémicos como profilaxis aunque sí se recomienda su uso en casos post-cirugía endoscópica nasal debido a la contaminación previa del sitio operatorio 12 . Los diuréticos como la acetazolamida pueden ser un adyuvante terapéu-tico útil en el caso de fístulas espontáneas con presión intracraneal elevada 13 .…”
Section: Discussionunclassified